2011
DOI: 10.1021/jz1016729
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Phosphonic Acids to CdSe Quantum Dots: A Solution NMR Study

Abstract: We use 1H and 31P solution nuclear magnetic resonance spectroscopy to analyze the binding of phosphonic acid ligands to wurtzite CdSe quantum dots (CdSe QDs). CdSe QDs synthesized with phosphonic acids as a surfactant have a ligand shell composed of phosphonic acid and phosphonic acid anhydride moieties. Titrations of as-synthesized QDs with excess oleic acid do not induce desorption of phosphonic species, whereas titration of oleic-acid-exchanged QDs with excess phosphonic acid shows that the latter quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
382
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(420 citation statements)
references
References 45 publications
30
382
2
Order By: Relevance
“…A weak NOE can even be seen to the end-chain methyl group. NOESY spectra with similar appearance have been reported for various sterically stabilized NCs, including gold nanoclusters capped with thiopronin [67], CdSe [61], and PbS [68] capped by oleate ligands, CdSe capped by phosphonate ligands [69], and InP capped with myristate ligands [70]. We thus conclude that the rotational mobility of a bound capping ligand molecule is dominated by the overall rotational diffusion behavior of the NC, which leads to the development of a strong and negative NOE.…”
Section: Noesysupporting
confidence: 78%
See 1 more Smart Citation
“…A weak NOE can even be seen to the end-chain methyl group. NOESY spectra with similar appearance have been reported for various sterically stabilized NCs, including gold nanoclusters capped with thiopronin [67], CdSe [61], and PbS [68] capped by oleate ligands, CdSe capped by phosphonate ligands [69], and InP capped with myristate ligands [70]. We thus conclude that the rotational mobility of a bound capping ligand molecule is dominated by the overall rotational diffusion behavior of the NC, which leads to the development of a strong and negative NOE.…”
Section: Noesysupporting
confidence: 78%
“…The bound oleate ligands are present on the NC surface in a 2 : 1 oleate/Cd stoichiometry relative to the excess Cd 2+ . In a separate study, Gomes et al determined that free OA does not readily displace octadecyl hydrogen phosphonate (ODPA -) bound to CdSe, as might be expected when comparing the pK a 1 values (∼2.6) for alkylphosphonic acids to the pK a of OA (∼5) [22]. Conversely, octadecylphosphonic acid (ODPA) will quantitatively exchange bound oleate on the CdSe surface.…”
Section: Carboxylic Acidsmentioning
confidence: 95%
“…Typically, resonances downfield from 4 ppm are easier to quantify such as the protons on the alkene of oleic acid at 5.3 ppm. 40,41 The current work quantifies ligand coverage by integration of the aromatic protons on the ferrocene derivatives (4−5 ppm) and referencing to an external standard. Since, the native ligands are primarily oleic acid with some residual octadecylphosphonic acid (ODPA), only the ferrocene resonances appear within the 4−5 ppm range (see Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…10,49 Dodecanoic acid is dissociatively adsorbed on the HfO 2 NC surface ( Figure 1A), a binding motif classified as NC(X) 2 . 39 Since it was already shown that ligand exchange processes with carboxylic acids are governed by acidity 4,10,54,55 and that it proved possible to transfer NaYF 4…”
Section: Resultsmentioning
confidence: 99%